Factors associated with nutritional status and risk in older adults in primary care institución - Bernui, Ivonne (2022)
Introduction. The Peruvian population is aging and this is associated with the deterioration of health. This process can be slowed or accelerated depending on the nutritional status. Objectives. To determine the factors associated with nutritional status and nutritional risk in a group of older adults. Methods. 265 older adults, free of cognitive impairment and able to communicate, were surveyed, cared for in primary care centers. The Mini Nutritional Assessment (MNA) test was applied and weight, height, arm, and calf circumference were measured. According to the score, the categories of the MNA were: ‘malnourished’ <17, at ‘risk of malnutrition’ between 17 - 23.5; > 23.5 ‘normal’. The nutritional status was also evaluated according to body mass index (BMI) with different cut-off points. Results. 79% of the respondents were women; 46% were between 70 and 79 years old. According to the MNA, only one person had ‘malnutrition’, 32.4% had ‘risk of malnutrition’. In contrast, according to the BMI, 50% were overweight according to the PAHO cut-off point and more than 80% were overweight according to the WHO cut-off point. A higher MNA score was found in men, and the ‘Risk of malnutrition’ was associated with higher consumption of medications. Conclusions. The nutritional status of half of the elderly was overweight according to BMI with the PAHO cut-off points, and a third of them had a risk of malnutrition according to the MNA instrument.